A trophic chain model with the inclusion of a nutrient, a prey and a predator, applied to the Lake Maracaibo ecosystem - Ortega, Horacio; Acosta, Antonio (Ciencia)
We present a trophic chain model that describes the invasion of Lemna obscura (a duckweed) in Lake Maracaibo. We consider a prey (the Lemna), with a predator (a herbivore), and we include an explicit equation for a nutrient. It is no teworthy that our model does not present some well- known paradoxes such as Rosenzweig”™s enrichment paradox, and Luck”™s unstable low prey paradox. We find that both stable nutrient and Lemna equilibrium populations are proportional for small nutrient in flux. For higher flux input, the Lemna population grows linearly with nutrients, but a stable predator population requires a threshold nutrient density. We suggest that the huge amounts of Lemna in Lake Maracaibo could be profitable as an important protein source for manufacture of manure, and also for animal and/or human nutrition.